1958
DOI: 10.1177/00220345580370032801
|View full text |Cite
|
Sign up to set email alerts
|

The Sex Difference in Tooth Calcification

Abstract: DURING the years of growth and development, girls are advanced over boys in a great many respects. They are earlier, on the average, in appearance of ossification centers; they are ahead in epiphysial union and the appearance of secondary sexual characteristics. While the direction of sexual dimorphism in the deciduous dentition may be somewhat questionable,' the fact that girls tend to be earlier in eruption of the permanent teeth is not. For white children of European ancestry, the average sex difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2
10

Year Published

1960
1960
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(68 citation statements)
references
References 7 publications
4
52
2
10
Order By: Relevance
“…The results from this study differ from previous findings of an advancement in root formation in females compared to males (Anderson et al, 1976;Garn et al, 1958;Haavikko, 1970;Liversidge, 2012;Liversidge et al, 2006;Moorrees et al, 1963;Nystrom et al, 2007;Thompson et al, 1975). Numerous previous studies report sexual dimorphism in timing between males and females in some teeth, particularly canines and third molar root stages (Anderson et al, 1976;Demirjian & Levesque, 1980;Garn et al, 1959;Haavikko, 1970;Levesque et al, 1981;Liversidge, 2008;Liversidge et al, 2006;Moorrees et al, 1963;Nystrom et al, 2007;Thompson et al, 1975).…”
Section: Comparison Between Male-female Within Groupscontrasting
confidence: 99%
“…The results from this study differ from previous findings of an advancement in root formation in females compared to males (Anderson et al, 1976;Garn et al, 1958;Haavikko, 1970;Liversidge, 2012;Liversidge et al, 2006;Moorrees et al, 1963;Nystrom et al, 2007;Thompson et al, 1975). Numerous previous studies report sexual dimorphism in timing between males and females in some teeth, particularly canines and third molar root stages (Anderson et al, 1976;Demirjian & Levesque, 1980;Garn et al, 1959;Haavikko, 1970;Levesque et al, 1981;Liversidge, 2008;Liversidge et al, 2006;Moorrees et al, 1963;Nystrom et al, 2007;Thompson et al, 1975).…”
Section: Comparison Between Male-female Within Groupscontrasting
confidence: 99%
“…Examining the first mandibular molar, Gleiser and Hunt (1955) stated their view that calcification was a more meaningful measure of maturity than was clinical emergence (eruption through the gingiva). Garn et al (1958), studying the mandibular premolars and molars of 255 children from the Fels longitudinal growth series, found girls to be advanced in dental development compared with boys, but by only 3% on average, and there was at least three times as much difference in skeletal maturation for those centers compared. Again using the Fels series, Garn et al (1960) found tooth calcification and tooth movement to be partially autonomous processes.…”
Section: Dental Development Studies: Generalmentioning
confidence: 99%
“…Chronological ages were recorded in decimal years, calculated as date of film minus date of birth. Dental scores and dental ages were calculated and assigned for each film based on the Bengston (1935) Variation in eruption, especially canines and premolars Brauer and Bahador (1942) Calcification distinct process from eruption Gleser and Hunt (1955) Calcification more meaningful measure than emergence; M1 growth spurt at one-third completed root length Garn et al (1958) Sex difference in skeletal maturation greater than dental Garn et al (1960) Tooth calcification and movement partially autonomous Nolla (1960) No sex difference in length of total tooth development Grøn (1962) Majority of teeth erupt at three-quarters root complete Moorrees et al (1963a) Canine has proportionally longer roots than do premolars at emergence; increased velocity of root elongation near emergence Moorrees et al (1963b) Sex difference in root maturation (longer for males) Steel (1965) Nonsignificant developmental correlations among P2, M2, and M3 Haavikko (1970) Large cross-sectional study of dental development and eruption, Helsinki Gustafson and Koch (1974) Diagrams for four stages of dental development Anderson et al (1975Anderson et al ( , 1976 and Thompson et al (1975) Canine shows greatest sex difference; boys more variable; canine mineralization delay, males, 20%; no acceleration of dental mineralization during puberty; dental development correlates more strongly with morphological than with skeletal maturation Demirjian and Levesque (1980) Sex differences in dental development and emergence Feasby (1981) Report of ''eruption surge'' not well correlated with increased root length Moorrees and Kent (1981) MZ twin root attainment age correlations of 0.90 Dean (1985) Root cone angles measured; suggestion of faster rate of increase in root length as root extends Harris and McKee (1990) Root development more sexually dimorphic than crown development Mappes et al (1992) Intersample dental mineralization differences despite hand-wrist ossification similarity Simpson and Kunos (1998) Modified Moorrees staging technique; root elongation of canine does not change in rate with emergence; rate of root formation of premolars more rapid later in development Liversidge et al (1999) Nonsignificant dental maturation differences between London Bangladeshi and Caucasian children …”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Previous studies (Swindler et al, 1982;Garn et al, 1958;Gleiser and Hunt, 1955; Swindler and Gavan, 1962;Hurme and VanWagenen, 1961;Fanning, 1961;Anderson et al, 1976;Schultz, 1935;Nolla, 1960) have identified sexual differences in the absolute but not relative timing of dental development and emergence within anthropoids. Swindler and co-workers (1982) have examined sexual differences in developmental pattern in nonhuman primates.…”
Section: Sexual Dimorphismmentioning
confidence: 95%